2017
DOI: 10.2174/1874312901711010053
|View full text |Cite
|
Sign up to set email alerts
|

Axial Spondyloarthritis and Cigarette Smoking

Abstract: Background:Smoking is one of the main environmental risk factors involved in several rheumatic diseases according to ACR 2014, it is included among the risk factors for severe axial spondyloarthritis.Objectives:The objective is to study the association between smoking and the activity of the disease, the functional impact and the severity of the axial spondyloarthritis.Methods:It is a transversal study with a descriptive and analytical aim, during the period between January 2014 and December 2015 conducted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Finally, regarding the duration of symptoms, there was no significant difference between the smoker and nonsmoker AS patients. This was consistent with the results found by Kaut et al [52] and Gaber et al [53]. However, Sakellariou et al [35] found that smoking is positively associated with the duration of inflammatory backache.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, regarding the duration of symptoms, there was no significant difference between the smoker and nonsmoker AS patients. This was consistent with the results found by Kaut et al [52] and Gaber et al [53]. However, Sakellariou et al [35] found that smoking is positively associated with the duration of inflammatory backache.…”
Section: Discussionsupporting
confidence: 91%
“…36 Smoking is an important public health concern and increases the disease burden in SpA. 37 There is an association between smoking and radiographic progression, disease activity, inflammation and syndesmophyte formation. 38 40 Smoking is a modifiable lifestyle factor.…”
Section: Resultsmentioning
confidence: 99%
“…Nearly half of the participants are smokers (46.8%). There is a strong relationship between smoking and the male gender and the severity of AS according to Kaut et al (26).…”
Section: Discussionmentioning
confidence: 98%